Application of Law no. 8 of 1999 concerning Consumer Protection to Minimize Consumer Disputes - Dede Hafirman Said; Azizatur Rahmah (LEGAL BRIEF, 2022)
The purpose of this study is to find out what efforts are made to minimize consumer disputes in ensuring legal certainty to protect consumers. The existence of a trade-in in both goods and services carried out by business actors often causes consumers to be harmed in terms of shopping which leads to a dispute between consumers and business actors. The research method used is normative juridical with a statutory approach whose data source is secondary data consisting of primary, secondary, and tertiary legal materials with data collection methods using library research. Data analysis is carried out from the hierarchy of laws and regulations. The problems in this scientific journal are aimed at how to apply Law No. 8 of 1999 concerning Consumer Protection in minimizing consumer losses, providing education to consumers, and being responsible for losses suffered by consumers. Regarding the efforts to resolve consumer disputes, it can be carried out through deliberation between the consumer and business actors, or assisted by third parties. The purpose of this study is to find out what efforts are made to minimize consumer disputes in ensuring legal certainty to protect consumers. The existence of a trade-in in both goods and services carried out by business actors often causes consumers to be harmed in terms of shopping which leads to a dispute between consumers and business actors. The research method used is normative juridical with a statutory approach whose data source is secondary data consisting of primary, secondary, and tertiary legal materials with data collection methods using library research. Data analysis is carried out from the hierarchy of laws and regulations. The problems in this scientific journal are aimed at how to apply Law No. 8 of 1999 concerning Consumer Protection in minimizing consumer losses, providing education to consumers, and being responsible for losses suffered by consumers. Regarding the efforts to resolve consumer disputes, it can be carried out through deliberation between the consumer and business actors, or assisted by third parties.